The Value of a Hole in Coal: Assessment of Seasonal Thermal Energy Storage and Recovery in Flooded Coal Mines - Jesus Perez Silva; Christopher McDermott; Andrew Fraser-Harris (Earth Science, Systems and Society)
Seasonal storage and extraction of heat in legacy coal mines could help decarbonize the space heating sector of many localities. The modelled evolution of a conceptual mine-water thermal scheme is analysed in this study, involving cyclical storage of heat in an enclosed underground coal mine. Conductive heat transport simulations are performed in a 3D model of a flooded room-and-pillar panel, based on typical mine layouts, to quantify the maximum thermal recovery from the host rock in different scenarios. We show that, by optimizing the seasonal management, from 25% to 45% of the energy transferred to the subsurface could be potentially recovered at the end of the first operational year. The modelled heat retrieval, achieved by subsurface cold-water circulation, does not consider the potentially enhancing effect of local advection around mine voids and applies to cases of relatively low dispersal of heat by the regional groundwater flow. The cumulative heat recovered from the modelled host rock could equal the thermal energy provided by the “mined” coal in less than 70 years. A comparison of the value of the original coal “mined,” at today’s prices, to a representative value for the heat recycled in the space created by its extraction, suggests that within less than 3 decades of thermal cycling similar monetary values are reached for the specific conditions modelled.